Applicability of low‐flow atmospheric pressure chemical ionization and photoionization mass spectrometry with a microfabricated nebulizer for neutral lipids. (25th March 2018) - Vrkoslav, Vladimír; Rumlová, Barbora; Strmeň, Timotej; Nekvasilová, Pavlína; Šulc, Miloslav; Cvačka, Josef
Abstract : Rationale: Mass spectrometry with atmospheric pressure chemical ionization (APCI) or photoionization (APPI) is widely used for neutral lipids involved in many fundamental processes in living organisms. Commercial APCI and APPI sources operate at high flow rates compatible with conventional high‐performance liquid chromatography (HPLC). However, lipid analysis is often limited by a small amount of sample, which requires low flow rate separations like capillary or micro‐HPLC. Therefore, APCI and APPI suitable for microliter‐per‐minute flow rates need to be developed and applied for neutral lipids. Methods: A micro‐APCI/APPI source with a heated chip nebulizer was assembled and mounted on a Thermo ion trap instrument. The ion source operated in APCI, APPI or dual mode was optimized for low microliter‐per‐minute sample flow rates. The source performance was investigated for squalene, wax esters, fatty acid methyl esters, triacylglycerols, and cholesterol. Results: The ion source behaved as a mass‐flow‐sensitive detector. Direct infusion of methyl oleate showed superior analytical figures of merit when compared with high‐flow ion sources. A detection limit of 200 pmol/mL and a linear dynamic range spanning three orders of magnitude were measured for micro‐APCI. The mass spectra of most lipids differed from high flow rate spectra. Unlike micro‐APCI, micro‐APPI spectra were complicated by odd‐electron species. Dual APCI/APPI mode did not show any benefits for neutral lipids. Applications for lipid samples were demonstrated. Conclusions: Micro‐APCI‐MS is a useful detection technique for neutral lipids at microliter‐per‐minute flow rates. It offers high sensitivity and high quality of spectra in direct infusion mode and promises successful utilization in capillary and micro‐HPLC applications.